DESIGNING AN AUDIO E-WORKSHEET TO TEACH LISTENING-SPEAKING FOR 7TH GRADERS - Aina Tsiqah; Restu Arini (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2022)
Listening is crucial to master as it reveals the ability to comprehend and produce effective communication. In fact, listening becomes an unfavorable skill and is considered less important that it does not appear in most school textbooks. This study aimed at the development of an English audio e-workbook as a languagelearning media to improve students’ listening skill in the classroom. This study is a mixed method study thatinvolved 25 students of 7th grade at junior high school in Ngawi, East Java, Indonesia. The result showed that the designed audio e- workbook showed a significant improvement on the student’s listening skill andconsidered properly to use and support students' listening skill based on the feedback availability and experts. The data was collected through interviews, questionnaires, and tests to determine the targets and needs of students. Most of the students achieved upgrading scores from the pre-test to their post-test. The pre-test resulted that students who passed the minimum grade, score averages is below 50.00, were below 50% while the post-test showed an upgrade of almost 75% of students having an increase in grades.